Cdc25B is transcriptionally inhibited by IER5 through the NF-YB transcription factor in irradiation-treated HeLa cells. Issue 4 (29th July 2021) - Ding, Lixin; Zhao, Xianzhe; Xiong, Qiang; Jiang, Xiaoyan; Liu, Xiaodan; Ding, Kuke; Zhou, Pingkun
Abstract: Cervical cancer (CC) is a type of pelvic malignant tumor that severely threatens women's health. Current evidence suggests that IER5, as a potential radiosensitizer, promotes irradiation-induced apoptosis in CC tissues in patients undergoing chemoradiotherapy. IER5 has been shown to be involved in the G2 /M-phase transition. In the present study, we used Cdc25B as the breakthrough point to explore the underlying mechanism of IER5 in the cell cycle regulation of radiation-damaged HeLa cells. IER5 was evidently upregulated after irradiation, but Cdc25B was significantly downregulated. In monoclonal IER5 -silenced HeLa cells, irradiation-induced downregulation of Cdc25B was attenuated. The effect of irradiation on Cdc25B promoter activity was determined by dual-luciferase reporter assays. The response elements on the Cdc25B promoter related to irradiation were predicted by JASPAR. These conserved sequences were mutated individually or in combination by splicing-by-overlap extension PCR, and their function was confirmed by dual-luciferase reporter assays. The enrichment efficiency of transcription factors after irradiation was determined by chromatin immunoprecipitation (ChIP) assay. Both Sp1/Sp3 and NF-YB binding sites were involved in irradiation-mediated regulation of Cdc25B . IER5 was involved in irradiation-mediated regulation of Cdc25B through the NF-YB binding site. Furthermore, ChIP assays showed that IER5 bound to the Cdc25B promoter, and the binding of IER5 to the Cdc25B promoter region in irradiation-induced HeLa cells induced the release of the coactivator p300 through interaction with NF-YB . Taken together, these findings indicate that IER5 is the transcriptional repressor that accelerates the downregulation of Cdc25B expression after irradiation.